Das Collegium Ruthenorum dei SS. Sergio e Bacco in Rom unter dem Protektorat der Habsburger - Uska, Ulyana (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2021)
"The Collegium Ruthenorum dei SS. Sergio e Bacco in Rome under the Habsburg Protectorate" - The article covers the process of formation of the Habsburg protectorate over national institutions in Rome, in particular the Ruthenian Foundation (Residence of the Basilian Prosecutors and Hospice) of St. Sergius and Bacchus, which came in 1884 under patronage of this dynasty. In 1897 an educational institution for Greek Catholic priests was established here - the Ruthenian Collegium (Ruthenorum), which trained highly specialized personnel for the Galician ecclesiastical province. Against the background of the foreign policy struggle between Austrian and Russian empire, the article reveals the complex internal church processes in the Greek Catholic dioceses, their interaction with public authorities, especially in Galicia.